Preparation method of soft skin care fabric
Through electrospinning and ultraviolet light reaction technology, irregular surfaces with gullies and grooves are formed, which solves the problem of poor effect of existing skin care fabrics in different environments, and achieves efficient hygroscopicity and anti-electromagnetic radiation performance, improving The overall performance of skin care fabrics is smooth.
Patent Information
- Application Number
- CN202411226651.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing skin care fabrics have average effects in different usage environments, and it is difficult to meet the needs of UV protection, moisturizing and electromagnetic radiation at the same time. There are fewer types on the market and insufficient performance.
Poly1,3-butadiene, TPU polyurethane, and modified composite nanoparticles are used to form semi-finished fibers through electrospinning, and under ultraviolet light, they are combined with modified end vinyl polydimethylsiloxane and ethyl orthosilicate. Reactions to form irregular surfaces with gullies and grooves, improving hygroscopicity and anti-electromagnetic radiation properties.
It significantly improves the moisture absorption and electromagnetic radiation resistance of the soft skin care fabric, forming a mechanical lock structure, ensuring the softness and protective performance of the fabric.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile materials, in particular to a method for preparing a soft and compliant skin-care fabric. Background Art
[0002] With the improvement of people's living standards, people have put forward higher requirements for textiles and clothing, not only for beautiful appearance and comfort, but also for whitening and skin care. Now all kinds of fabrics are sold in huge quantities in the market with high added value, which makes the market demand for antibacterial, dustproof, moisturizing, radiation-proof and other types of fabrics even greater, and the performance requirements for such clothing are also getting higher and higher.
[0003] People have different requirements for the performance of skin care fabrics in different usage environments. For example, in strong light environments, fabrics need to be able to block ultraviolet rays; in radiation environments, fabrics need to be able to block radiation; in dry environments, fabrics need to be able to retain moisture; in humid and hot environments, fabrics need to be dry and breathable, etc. Currently, there are few types of skin care fabrics on the market, and the effects are average. Therefore, skin care fabrics have huge market demand and research and development prospects. Summary of the invention
[0004] The object of the present invention is to provide a soft skin-care fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a soft skin-care fabric, characterized in that the soft skin-care fabric is prepared by electrostatically spinning poly 1,3-butadiene, TPU polyurethane, polyethylene terephthalate, and modified composite nanoparticles to form semi-finished fibers, and then reacting the semi-finished fibers with modified vinyl-terminated polydimethylsiloxane and tetraethyl orthosilicate under ultraviolet light to form a weaving fabric.
[0006] As an optimization, the modified composite nanoparticles are prepared by reacting ferric chloride, ferrous chloride and tetrabutyl titanate, and the composite nanoparticles are reacted with p-chlorophenyltrimethoxysilane and mercaptovinyl polysiloxane in sequence to obtain the composite nanoparticles.
[0007] As an optimization, the mercaptovinyl polysiloxane is prepared by reacting hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane and then reacting with 4-hydroxythiophenol.
[0008] As an optimization, the modified vinyl-terminated polydimethylsiloxane is prepared by reacting vinyl-terminated polydimethylsiloxane with allyl dimethoxysilane and triethoxysilane in sequence.
[0009] As an optimization, the preparation method of the soft skin care fabric includes the following preparation steps: (1) 4-hydroxythiophenol, vinyl polysiloxane and tetrahydrofuran are mixed uniformly in a mass ratio of 1:4:20-1:5:25, and triphenylphosphine (0.01-0.03 times the mass of 4-hydroxythiophenol) and diisopropyl azodicarboxylate (0.01-0.03 times the mass of 4-hydroxythiophenol) are added at 0-5°C, and the mixture is stirred at 10-30°C and 1500-2000 r / min for 8-12 hours. Then, hexamethyldisiloxane (4-5 times the mass of 4-hydroxythiophenol) and pure water (6-8 times the mass of 4-hydroxythiophenol) are added and stirred for 20-30 minutes. The mixture is allowed to stand for 10-15 minutes, and the oil phase is separated and dried at 10-30°C and 1-10 Pa for 8-10 hours to obtain mercapto vinyl polysiloxane. (2) The composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 3:1:15:3-4:1:20:4, stirred at 10-30°C and 800-1000 r / min for 40-50 min, and dried at -10--1°C and 1-10 Pa for 8-10 h to obtain pre-modified composite nanoparticles. The pre-modified composite nanoparticles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed in a mass ratio of 1:1:15:5-1:2:18:6, and the pre-modified A 3-5% potassium hydroxide solution with a mass fraction of 1-1.2 times the mass of the modified composite nanoparticles was added, stirred at 10-30°C and 300-500 r / min for 20-30 min, heated to 120-130°C and maintained for 3-4 h, and then heated to 160-170°C and maintained for 3-4 h. After cooling to room temperature, 3-5% hydrochloric acid was added to adjust the pH to 6.9-7.1, filtered, washed with pure water and anhydrous ethanol for 3-5 times respectively, and dried at 10-30°C and 1-10 Pa for 8-10 h to obtain modified composite nanoparticles. (3) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol are uniformly mixed in a mass ratio of 1:1:1:1:7:7:0.1:4 to 1:1:1:1:9:9:0.2:2, and electrospinning is performed to obtain semi-finished fiber; (4) The semi-finished fiber is immersed in ethanol with a mass fraction of 60-70% at 20-30°C, and irradiated with ultraviolet light for 3-5 min using a 300-400 W high-pressure mercury lamp at 2-3 cm above the semi-finished fiber. Then, the irradiation is continued and 0.3-0.4 times the mass of the semi-finished fiber of tetraethyl orthosilicate and 0.1-0.2 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane are added. The fiber is ultrasonically treated at 30-40 kHz for 30-40 min. The fiber is taken out and washed with pure water and anhydrous ethanol for 3-5 times respectively, and dried at -10--1°C and 1-10 Pa for 8-10 h to obtain a soft skin-care fiber. The soft skin-care fiber is woven to obtain an anti-ultraviolet and anti-wrinkle fabric.
[0010] As an optimization, the preparation method of the vinyl polysiloxane in step (1) is as follows: in a nitrogen atmosphere, hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane, anhydrous ethanol and acetic acid with a mass fraction of 15-20% are uniformly mixed in a mass ratio of 1:3:2:8:5-1:4:2:10:7, stirred at 30-40°C and 500-800r / min for 60-80min, then hexamethyldisiloxane with a mass of 3-4 times that of hydroxymethyltriethoxysilane is added and stirred for 20-30min, allowed to stand for 10-15min, the oil phase is separated and allowed to stand at 10-30°C and 1-2kPa for 8-10h to prepare the polysiloxane.
[0011] As an optimization, the preparation method of the composite nanoparticles in step (2) is: ferric chloride, ferrous chloride, tetrabutyl titanate and pure water are uniformly mixed in a mass ratio of 5:2:4:25-5:3:5:30, heated to 80-90°C in a nitrogen atmosphere, stirred at 1500-2000 r / min for 3-5 min, added with 50% ammonia water with a mass fraction of 2-3 times the mass of ferric chloride, continued to stir at 1500-2000 r / min for 15-20 min, filtered and washed with pure water for 3-5 times, and dried at 60-70°C for 3-4 h to prepare the composite nanoparticles.
[0012] As an optimization, the process parameters of the electrospinning in step (3) are: voltage 15~20 kV, spinning speed 40~45 μL / min, receiving distance 15~17 cm, spinneret aperture 0.8~0.9 m, temperature 50~55°C.
[0013] As an optimization, the preparation method of the modified terminal vinyl polydimethylsiloxane in step (4) is: vinyl-terminated polydimethylsiloxane and n-hexane are uniformly mixed in a mass ratio of 1:5 to 1:8, and then 0.01 to 0.03 times the mass of vinyl-terminated polydimethylsiloxane and 0.5 to 0.7 times the mass of vinyl-terminated polydimethylsiloxane are added, stirring and refluxing at 70 to 80° C. and 500 to 800 r / min for 4 to 6 hours, and then 0.08 to 0.1 times the mass of vinyl-terminated polydimethylsiloxane is added, stirring and refluxing is continued for 4 to 6 hours, and then standing at 20 to 30° C. and 1 to 2 kPa for 3 to 4 hours to prepare the modified terminal vinyl polydimethylsiloxane.
[0014] As an optimization, the weaving method of step (4) is: twisting the soft skin care fiber to 50-70D through a fiber weaving machine, and then weaving it into 100-150g / m 2 Heavyweight fabric.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the soft skin-care fabric, the present invention firstly electrostatically spins poly 1,3-butadiene, TPU polyurethane, polyethylene terephthalate and modified composite nanoparticles to form semi-finished fibers, and then reacts the semi-finished fibers with modified vinyl-terminated polydimethylsiloxane and tetraethyl orthosilicate under ultraviolet light to weave the soft skin-care fabric.
[0016] Firstly, ferric chloride, ferrous chloride and tetrabutyl titanate are reacted to obtain composite nanoparticles, the composite nanoparticles are pre-modified with p-chlorophenyltrimethoxysilane and then reacted with mercaptovinyl polysiloxane to obtain modified composite nanoparticles, the modified composite nanoparticles can photocatalytically degrade ester groups and polyethylene glycol in the fiber, so that the fiber surface forms an irregular surface with gullies and grooves, the mercaptovinyl polysiloxane is connected by forming phenyl sulfide, the phenyl sulfide group can be broken under ultraviolet light to form sulfur free radicals, which triggers the polymerization of the carbon-carbon double bonds of vinyl and 1,3-butadiene on the mercaptovinyl polysiloxane to form a cross-linked network structure, so that the irregular surface with gullies and grooves is cured and stabilized, the ethyl orthosilicate and the modified terminal ethyl The alkoxy silicon on the edge of alkenyl polydimethylsiloxane is hydrolyzed into silanol group under the photocatalysis of composite nanoparticles, and connected to the modified composite nanoparticles to form silica gel with good hygroscopicity. The irregular surface with gullies and grooves increases the filling amount of silica gel. After the irregular surface is filled with silica gel, a mechanical locking structure is formed, which makes the silica gel not easy to lose, thereby improving the hygroscopicity of the soft skin care fabric. The mercaptovinyl polysiloxane grafted on the modified composite nanoparticles makes the modified composite nanoparticles not easy to agglomerate, improves the dispersion of the modified composite nanoparticles, and improves the absorption and reflection effect of the modified composite nanoparticles on electromagnetic radiation, thereby improving the anti-electromagnetic radiation performance of the soft skin care fabric.
[0017] Secondly, the modified terminal vinyl polydimethylsiloxane is prepared by reacting terminal vinyl polydimethylsiloxane with allyl dimethoxysilane and triethoxysilane in sequence. The prepared modified terminal vinyl polydimethylsiloxane has a longer methoxysilane chain segment at the edge. The longer methoxysilane chain segment is hydrolyzed into silanol, making the modified terminal vinyl polydimethylsiloxane easier to connect with the silica gel formed by the modified composite nanoparticles or tetraethyl orthosilicate, thereby improving the effect of the terminal vinyl polydimethylsiloxane on reducing the surface energy of the fiber surface, thereby improving the softness of the soft skin care fabric. At the same time, the longer methoxysilane chain segment can promote the formation and adhesion of tetraethyl orthosilicate to form silica gel, thereby improving the moisture absorption performance of the soft skin care fabric. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the soft skin care fabrics prepared in the following examples are as follows: Softness: The soft skin-care fabrics obtained in each embodiment and the comparative material are taken in the same size, shape and thickness, and the softness is tested by a swing-type fabric softness tester according to the ZBW04002-86 standard.
[0020] Moisturizing performance: The soft skin-care fabrics obtained in each embodiment and the comparative material of the same size, shape and thickness are placed in the same environment with the same humidity. The humidity on the surface of the material is measured after the same period of time, and the humidity difference is recorded as surface humidity minus ambient humidity.
[0021] Anti-electromagnetic radiation performance: The soft skin-care fabrics obtained in each embodiment and the comparative material are taken to have the same size, shape and thickness, and a radiation source under the same conditions is placed on one side of the material. The power density is detected on the side with the radiation source and the side without the radiation source by a radiation detector, and the shielding rate is calculated as (power density on the side with the radiation source - power density on the side without the radiation source) / power density on the side with the radiation source.
[0022] Example 1 A method for preparing a soft and compliant skin-care fabric, the method for preparing the soft and compliant skin-care fabric mainly comprises the following preparation steps: (1) In a nitrogen atmosphere, hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane, anhydrous ethanol and 15% acetic acid were mixed in a mass ratio of 1:3:2:8:5, stirred at 30°C and 500 r / min for 80 min, and then hexamethyldisiloxane (3 times the mass of hydroxymethyltriethoxysilane) was added and stirred for 30 min. The mixture was allowed to stand for 15 min, and the oil phase was separated and allowed to stand at 10°C and 1 kPa for 10 h to obtain vinyl polysiloxane. 4-Hydroxythiophenol and vinyl The polysiloxane and tetrahydrofuran were mixed evenly in a mass ratio of 1:4:20, and triphenylphosphine and diisopropyl azodicarboxylate with a mass of 0.01 times that of 4-hydroxythiophenol were added at 0°C, and the mixture was stirred at 10°C and 1500 r / min for 12 hours. Then, hexamethyldisiloxane with a mass of 4 times that of 4-hydroxythiophenol and pure water with a mass of 6 times that of 4-hydroxythiophenol were added and the mixture was stirred for 30 minutes. The mixture was allowed to stand for 10 minutes, and the oil phase was separated and dried at 10°C and 1 Pa for 10 hours to obtain mercaptovinyl polysiloxane. (2) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed in a mass ratio of 5:2:4:25, heated to 80°C in a nitrogen atmosphere, stirred at 1500 r / min for 5 min, added with 50% ammonia water with a mass fraction twice that of the ferric chloride, continued to stir at 1500 r / min for 20 min, filtered and washed with pure water for 3 times, dried at 60°C for 4 h to obtain composite nanoparticles, composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 3:1:15:3, stirred at 10°C and 800 r / min for 50 min, dried at -10°C and 1 Pa The pre-modified composite nanoparticles were prepared by drying for 10 hours, and the pre-modified composite nanoparticles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:1:15:5, and then a 5% potassium hydroxide solution with a mass fraction of 1 times the mass of the pre-modified composite nanoparticles was added, and the mixture was stirred at 10°C and 300r / min for 30 minutes, and the temperature was raised to 120°C and maintained for 4 hours, and the temperature was further raised to 160°C and maintained for 4 hours. After cooling to room temperature, 3% hydrochloric acid was added to adjust the pH to 6.9, and the mixture was filtered and washed with pure water and anhydrous ethanol for 3 times respectively, and dried at 10°C and 1Pa for 10 hours to prepare modified composite nanoparticles. (3) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:7:7:0.1:4, and subjected to electrospinning at a voltage of 15 kV, a spinning speed of 40 μL / min, a receiving distance of 15 cm, a spinneret aperture of 0.8 m, and a temperature of 50 °C to obtain a semi-finished fiber; (4) Vinyl-terminated polydimethylsiloxane and n-hexane were mixed evenly in a mass ratio of 1:5, and then 0.01 times the mass of vinyl-terminated polydimethylsiloxane and 0.5 times the mass of allyldimethoxysilane were added, and the mixture was stirred and refluxed at 70°C and 500 r / min for 6 hours. Then, 0.08 times the mass of vinyl-terminated polydimethylsiloxane was added, and the mixture was stirred and refluxed for 6 hours. The mixture was allowed to stand at 20°C and 1 kPa for 4 hours to obtain modified vinyl-terminated polydimethylsiloxane. The semi-finished fiber was immersed in a 20°C, In 60% by mass ethanol, a 400W high-pressure mercury lamp was used to irradiate the semi-finished fiber with ultraviolet light for 3 minutes at a position 2 cm above the semi-finished fiber. Then, the irradiation was continued and 0.3 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.1 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane were added. The fiber was ultrasonically treated at 30kHz for 40 minutes. The fiber was taken out and washed with pure water and anhydrous ethanol for 3 times respectively. The fiber was dried at -10℃ and 1Pa for 10 hours to obtain a soft skin-care fiber. The soft skin-care fiber was twisted to 50D by a fiber braiding machine and then woven into a 120g / m 2Heavy weight fabric, made with UV protection and wrinkle resistance.
[0023] Example 2 A method for preparing a soft and compliant skin-care fabric, the method for preparing the soft and compliant skin-care fabric mainly comprises the following preparation steps: (1) In a nitrogen atmosphere, hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane, anhydrous ethanol and 18% acetic acid were mixed in a mass ratio of 1:3.5:2:9:6, stirred at 35°C and 650 r / min for 70 min, and then hexamethyldisiloxane (3.5 times the mass of hydroxymethyltriethoxysilane) was added and stirred for 25 min. The mixture was allowed to stand for 12 min, and the oil phase was separated and allowed to stand at 20°C and 1.5 kPa for 9 h to obtain vinyl polysiloxane. 4-Hydroxythiophenol and ethylene The polysiloxane and tetrahydrofuran were mixed evenly in a mass ratio of 1:4.5:22, and triphenylphosphine with a mass of 0.02 times that of 4-hydroxythiophenol and diisopropyl azodicarboxylate with a mass of 0.02 times that of 4-hydroxythiophenol were added at 2°C, and the mixture was stirred at 20°C and 1800r / min for 10 hours. Then, hexamethyldisiloxane with a mass of 4.5 times that of 4-hydroxythiophenol and pure water with a mass of 7 times that of 4-hydroxythiophenol were added and the mixture was stirred for 25 minutes. The mixture was allowed to stand for 12 minutes, and the oil phase was separated and dried at 20°C and 5Pa for 9 hours to obtain mercaptovinyl polysiloxane. (2) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed in a mass ratio of 5:2:4.5:27, heated to 85°C in a nitrogen atmosphere, stirred at 1800 r / min for 4 min, added with 50% ammonia water (2.5 times the mass of ferric chloride), stirred at 1800 r / min for 18 min, filtered and washed with pure water for 4 times, dried at 65°C for 3.5 h, and composite nanoparticles were obtained. Composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 3.5:1:18:3.5, stirred at 20°C and 900 r / min for 45 min, and dried at -5°C and 5P a dried for 9 hours to obtain pre-modified composite nanoparticles, the pre-modified composite nanoparticles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:1.5:16:5.5, and then a 4% potassium hydroxide solution with a mass fraction of 1.1 times the mass of the pre-modified composite nanoparticles was added, stirred at 20°C and 400r / min for 25 minutes, heated to 125°C and maintained for 3.5 hours, and continued to heat to 165°C and maintained for 3.5 hours. After cooling to room temperature, 4% hydrochloric acid was added to adjust the pH to 7, filtered and washed with pure water and anhydrous ethanol for 4 times respectively, and dried at 20°C and 5Pa for 9 hours to obtain modified composite nanoparticles; (3) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:8:8:0.15:3, and subjected to electrospinning at a voltage of 18 kV, a spinning speed of 42 μL / min, a receiving distance of 16 cm, a spinneret aperture of 0.8 m, and a temperature of 52 °C to obtain a semi-finished fiber; (4) Vinyl-terminated polydimethylsiloxane and n-hexane were mixed evenly in a mass ratio of 1:6, and then 0.02 times the mass of vinyl-terminated polydimethylsiloxane and 0.6 times the mass of allyldimethoxysilane were added, and the mixture was stirred and refluxed at 75°C and 600 r / min for 5 hours. Then, 0.09 times the mass of vinyl-terminated polydimethylsiloxane was added, and the mixture was stirred and refluxed for 5 hours. The mixture was allowed to stand at 25°C and 1.5 kPa for 3.5 hours to obtain modified vinyl-terminated polydimethylsiloxane. The semi-finished fiber was immersed in a 25°C , in 65% ethanol by mass, use a 350W high-pressure mercury lamp to irradiate the semi-finished fiber with ultraviolet light for 4 minutes at a position 2.5 cm above the semi-finished fiber, continue to irradiate and add 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane, ultrasonically treat at 35kHz for 35 minutes, take out and wash with pure water and anhydrous ethanol 4 times respectively, dry at -5℃, 5Pa for 9 hours to obtain soft skin care fiber, twist the soft skin care fiber to 60D through a fiber braiding machine, and weave it into 120g / m 2 Heavy weight fabric, made with UV protection and wrinkle resistance.
[0024] Example 3 A method for preparing a soft and compliant skin-care fabric, the method for preparing the soft and compliant skin-care fabric mainly comprises the following preparation steps: (1) In a nitrogen atmosphere, hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane, anhydrous ethanol and 20% acetic acid were mixed in a mass ratio of 1:4:2:10:7, stirred at 30°C and 500 r / min for 80 min, and then hexamethyldisiloxane (3 times the mass of hydroxymethyltriethoxysilane) was added and stirred for 30 min. The mixture was allowed to stand for 15 min, and the oil phase was separated and allowed to stand at 10°C and 1 kPa for 10 h to obtain vinyl polysiloxane. 4-Hydroxythiophenol and ethylene The polysiloxane and tetrahydrofuran were mixed evenly in a mass ratio of 1:5:25, and triphenylphosphine with a mass of 0.03 times that of 4-hydroxythiophenol and diisopropyl azodicarboxylate with a mass of 0.03 times that of 4-hydroxythiophenol were added at 5°C, and the mixture was stirred at 30°C and 2000r / min for 8h, and then hexamethyldisiloxane with a mass of 5 times that of 4-hydroxythiophenol and pure water with a mass of 8 times that of 4-hydroxythiophenol were added and stirred for 20min, and the mixture was allowed to stand for 10min, and the oil phase was separated and dried at 30°C and 10Pa for 8h to obtain mercaptovinyl polysiloxane; (2) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed in a mass ratio of 5:3:5:30, heated to 90°C in a nitrogen atmosphere, stirred at 2000 r / min for 3 min, added with 50% ammonia water (3 times the mass of ferric chloride), stirred at 2000 r / min for 15 min, filtered and washed with pure water for 3 times, dried at 70°C for 3 h to obtain composite nanoparticles, composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 4:1:20:4, stirred at 30°C and 1000 r / min for 40 min, dried at -1°C and 10 Pa The pre-modified composite nanoparticles were prepared by drying for 8 hours, and the pre-modified composite nanoparticles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:2:18:6, and then a 5% potassium hydroxide solution with a mass fraction of 1.2 times the mass of the pre-modified composite nanoparticles was added, and the mixture was stirred at 30°C and 500r / min for 20 minutes, and the temperature was raised to 130°C and maintained for 3 hours, and the temperature was further raised to 170°C and maintained for 3 hours. After cooling to room temperature, 5% hydrochloric acid was added to adjust the pH to 7.1, filtered, washed with pure water and anhydrous ethanol for 5 times respectively, and dried at 30°C and 10Pa for 8 hours to obtain modified composite nanoparticles. (3) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:9:9:0.2:2, and subjected to electrospinning at a voltage of 20 kV, a spinning speed of 45 μL / min, a receiving distance of 17 cm, a spinneret aperture of 0.9 m, and a temperature of 55 °C to obtain semi-finished fiber; (4) Vinyl-terminated polydimethylsiloxane and n-hexane were mixed evenly in a mass ratio of 1:8, and then 0.03 of the mass of vinyl-terminated polydimethylsiloxane and 0.7 times the mass of allyldimethoxysilane were added, and the mixture was stirred and refluxed at 80°C and 800 r / min for 4 h. Then, 0.1 times the mass of vinyl-terminated polydimethylsiloxane was added, and the mixture was stirred and refluxed for 6 h. The mixture was allowed to stand at 30°C and 2 kPa for 3 h to obtain modified vinyl-terminated polydimethylsiloxane. The semi-finished fiber was immersed in a 30°C, In 70% by mass ethanol, a 400W high-pressure mercury lamp was used to irradiate the semi-finished fiber with ultraviolet light for 5 minutes at a position 3 cm above the semi-finished fiber. Then, the irradiation was continued and 0.4 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.2 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane were added. The fiber was ultrasonically treated at 40kHz for 30 minutes. The fiber was taken out and washed 5 times with pure water and 5 times with anhydrous ethanol respectively. The fiber was dried at -1°C and 10Pa for 8 hours to obtain a soft skin-care fiber. The soft skin-care fiber was twisted to 70D by a fiber braiding machine and then woven into a 120g / m 2 Heavy weight fabric, made with UV protection and wrinkle resistance.
[0025] Comparative Example 1 A method for preparing a soft and compliant skin-care fabric, the method for preparing the soft and compliant skin-care fabric mainly comprises the following preparation steps: (1) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed in a mass ratio of 5:2:4.5:27, heated to 85°C in a nitrogen atmosphere, stirred at 1800 r / min for 4 min, added with 50% ammonia water with a mass fraction of 2.5 times the mass of ferric chloride, continued to stir at 1800 r / min for 18 min, filtered and washed with pure water for 4 times, dried at 65°C for 3.5 h, and obtained composite nanoparticles; composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 4:1:20:4, stirred at 30°C, 1000 r / min for 40 min, and dried at -1°C, 10 Pa for 8 h to obtain modified composite nanoparticles; (2) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:8:8:0.15:3, and subjected to electrospinning at a voltage of 18 kV, a spinning speed of 42 μL / min, a receiving distance of 16 cm, a spinneret aperture of 0.8 m, and a temperature of 52 °C to obtain a semi-finished fiber; (3) Vinyl-terminated polydimethylsiloxane and n-hexane were mixed evenly in a mass ratio of 1:6, and then 0.02 times the mass of vinyl-terminated polydimethylsiloxane and 0.6 times the mass of allyldimethoxysilane were added, and the mixture was stirred and refluxed at 75°C and 600 r / min for 5 hours. Then, 0.09 times the mass of vinyl-terminated polydimethylsiloxane was added, and the mixture was stirred and refluxed for 5 hours. The mixture was allowed to stand at 25°C and 1.5 kPa for 3.5 hours to obtain modified vinyl-terminated polydimethylsiloxane. The semi-finished fiber was immersed in a 25°C , in 65% ethanol by mass, use a 350W high-pressure mercury lamp to irradiate the semi-finished fiber with ultraviolet light for 4 minutes at a position 2.5 cm above the semi-finished fiber, continue to irradiate and add 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane, ultrasonically treat at 35kHz for 35 minutes, take out and wash with pure water and anhydrous ethanol 4 times respectively, dry at -5℃, 5Pa for 9 hours to obtain soft skin care fiber, twist the soft skin care fiber to 60D through a fiber braiding machine, and weave it into 120g / m 2 Heavy weight fabric, made with UV protection and wrinkle resistance.
[0026] Comparative Example 2 The preparation method of the soft skin-care fabric of Comparative Example 2 is different from that of Example 2 only in step (2). Step (2) is modified as follows: ferric chloride, ferrous chloride, tetrabutyl titanate and pure water are mixed uniformly in a mass ratio of 5:2:4.5:27, heated to 85°C in a nitrogen atmosphere, stirred at 1800 r / min for 4 min, 50% ammonia water with a mass fraction of 2.5 times the mass of ferric chloride is added, stirred at 1800 r / min for 18 min, filtered and washed with pure water 4 times, dried at 65°C for 3.5 h, and composite nanoparticles are obtained. The particles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:1.5:16:5.5, and then a 4% potassium hydroxide solution with a mass fraction of 1.1 times the mass of the composite nanoparticles was added, stirred at 20°C, 400r / min for 25min, heated to 125°C and maintained for 3.5h, continued to heat to 165°C and maintained for 3.5h, cooled to room temperature, added with a mass fraction of 4% hydrochloric acid to adjust the pH to 7, filtered and washed with pure water and anhydrous ethanol 4 times each, dried at 20°C, 5Pa for 9h, and obtained modified composite nanoparticles. The remaining steps were the same as in Example 2.
[0027] Comparative Example 3 The preparation method of the soft skin-care fabric of Comparative Example 3 is different from that of Example 3 only in step (4). Step (4) is modified as follows: vinyl-terminated polydimethylsiloxane and n-hexane are mixed uniformly in a mass ratio of 1:6, and then 0.02 times the mass of vinyl-terminated polydimethylsiloxane and 0.09 times the mass of triethoxysilane are added, and the mixture is stirred and refluxed at 75° C. and 600 r / min for 5 h, and then allowed to stand at 25° C. and 1.5 kPa for 3.5 h to obtain modified vinyl-terminated polydimethylsiloxane; the semi-finished fiber is immersed in 2 5℃, in 65% by mass ethanol, use a 350W high-pressure mercury lamp to irradiate the semi-finished fiber with ultraviolet light for 4 minutes at a position 2.5cm above the semi-finished fiber, continue irradiating and add 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane, ultrasonically treat at 35kHz for 35 minutes, take out and wash with pure water and anhydrous ethanol 4 times respectively, dry at -5℃, 5Pa for 9 hours to obtain a soft skin care fiber, twist the soft skin care fiber to 60D through a fiber braiding machine, and weave it into 120g / m 2 The remaining steps are the same as those in Example 2.
[0028] Comparative Example 4 The preparation method of the soft skin-care fabric of Comparative Example 4 is different from that of Example 3 only in step (4). Step (4) is modified as follows: vinyl-terminated polydimethylsiloxane and n-hexane are uniformly mixed in a mass ratio of 1:6, and then 0.02 times the mass of vinyl-terminated polydimethylsiloxane and 0.6 times the mass of allyldimethoxysilane are added, and the mixture is stirred and refluxed at 75° C. and 600 r / min for 5 h, and then allowed to stand at 25° C. and 1.5 kPa for 3.5 h to obtain modified vinyl-terminated polydimethylsiloxane; the semi-finished fiber is immersed in At 25°C, in 65% ethanol by mass, a 350W high-pressure mercury lamp was used to irradiate the semi-finished fiber with ultraviolet light for 4 minutes at a position 2.5 cm above the semi-finished fiber. Then, the irradiation was continued and 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane were added. The fiber was ultrasonically treated at 35kHz for 35 minutes. The fiber was taken out and washed 4 times with pure water and 4 times with anhydrous ethanol respectively. The fiber was dried at -5°C and 5Pa for 9 hours to obtain a soft skin-care fiber. The soft skin-care fiber was twisted to 60D by a fiber braiding machine and then woven into a 120g / m 2 The remaining steps are the same as those in Example 2.
[0029] Comparative Example 5 A method for preparing a soft and compliant skin-care fabric, the method for preparing the soft and compliant skin-care fabric mainly comprises the following preparation steps: (1) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed uniformly in a mass ratio of 5:2:4.5:27, heated to 85°C in a nitrogen atmosphere, stirred at 1800 r / min for 4 min, added with 50% ammonia water (2.5 times the mass of ferric chloride), stirred at 1800 r / min for 18 min, filtered and washed with pure water for 4 times, and dried at 65°C for 3.5 h to obtain composite nanoparticles; (2) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:8:8:0.15:3, and subjected to electrospinning at a voltage of 18 kV, a spinning speed of 42 μL / min, a receiving distance of 16 cm, a spinneret aperture of 0.8 m, and a temperature of 52 °C to obtain a semi-finished fiber; (3) The semi-finished fiber was immersed in 65% ethanol at 25°C, and irradiated with ultraviolet light for 4 min at 2.5 cm above the semi-finished fiber using a 350W high-pressure mercury lamp. The irradiation was continued and 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of vinyl-terminated polydimethylsiloxane were added. The fiber was ultrasonically treated at 35kHz for 35 min. The fiber was taken out and washed with pure water and anhydrous ethanol for 4 times each. The fiber was dried at -5°C and 5Pa for 9 h to obtain a soft skin-care fiber. The soft skin-care fiber was twisted to 60D by a fiber braiding machine and then woven into a 120g / m 2 Heavy weight fabric, made with UV protection and wrinkle resistance.
[0030] Effect example Table 1 below shows the performance analysis results of the softness, moisturizing properties and anti-electromagnetic radiation properties of the soft skin-care fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0031] Table 1 Softness Humidity difference Shielding rate Softness Humidity difference Shielding rate Example 1 Level 4 10.8% 98.2% Comparative Example 2 Level 4 6.5% 88.2% Example 2 Level 4 11.0% 98.5% Comparative Example 3 Level 3 4.6% 98.5% Example 3 Level 4 11.1% 98.3% Comparative Example 4 Level 3 10.6% 98.0% Comparative Example 1 Level 4 7.1% 97.8% Comparative Example 5 Level 3 4.4% 85.9% From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the soft skin-care fabric prepared by the present invention has good softness, moisturizing and anti-electromagnetic radiation performance.
[0032] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the humidity difference of Examples 1, 2, 3 is higher than that of Comparative Example 1, which indicates that the pre-modified composite nanoparticles and mercaptovinyl polysiloxane react to obtain modified composite nanoparticles, and the modified composite nanoparticles can photocatalytically degrade the ester group and polyethylene glycol in the fiber, so that the fiber surface forms an irregular surface with gullies and grooves, and the mercaptovinyl polysiloxane is connected by forming phenylene sulfide, and the phenylene sulfide group breaks under ultraviolet light to form sulfur free radicals, which triggers the polymerization of the carbon-carbon double bonds of the vinyl group and 1,3-butadiene on the mercaptovinyl polysiloxane to form a cross-linked network structure, so that the irregular surface with gullies and grooves is cured and stabilized, and the ethyl orthosilicate and the modified The alkoxy silicon on the edge of the vinyl-terminated polydimethylsiloxane is hydrolyzed into silanol groups under the photocatalysis of the composite nanoparticles, and is connected to the modified composite nanoparticles to form a silica gel with good hygroscopicity. The irregular surface with gullies and grooves increases the filling amount of the silica gel. After the irregular surface is filled with the silica gel, a mechanical locking structure is formed, which makes the silica gel not easy to lose, thereby improving the hygroscopicity of the soft skin care fabric. From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the humidity difference and shielding rate of Examples 1, 2, 3 are higher than those of Comparative Example 2, which shows that the modified composite nanoparticles are pre-modified and can be subsequently reacted with mercaptovinyl polysiloxane. The mercaptovinyl polysiloxane is reacted with the mercaptovinyl polysiloxane through The connection is formed by forming phenyl sulfide, and the phenyl sulfide group can form sulfur free radicals under ultraviolet light to initiate the polymerization of double bonds, so that the irregular surface with gullies and grooves is cured stably, the load on the silica gel is increased, and a mechanical locking structure is formed, thereby improving the hygroscopic performance of the soft skin care fabric; secondly, the organic groups on the surface of the modified composite nanoparticles have good compatibility with the remaining components, so that the modified composite nanoparticles are not easy to agglomerate, the dispersion of the modified composite nanoparticles is improved, and the absorption and reflection effects of the modified composite nanoparticles on electromagnetic radiation are improved, thereby improving the anti-electromagnetic radiation performance of the soft skin care fabric; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Column 3, it can be found that Examples 1, 2, 3 have good compatibility with the other components, so that the modified composite nanoparticles are not easy to agglomerate, the dispersion of the modified composite nanoparticles is improved, and the absorption and reflection effects of the modified composite nanoparticles on electromagnetic radiation are improved, thereby improving the anti-electromagnetic radiation performance of the soft skin care fabric. The softness is higher than that of comparative example 3, which indicates that allyl dimethoxysilane is added during the modification process of the vinyl-terminated polydimethylsiloxane, and the obtained modified vinyl-terminated polydimethylsiloxane has a longer methoxysilane segment at the edge, and the longer methoxysilane segment is hydrolyzed into silanol, so that the modified vinyl-terminated polydimethylsiloxane is easier to connect with the silica gel formed by the modified composite nanoparticles or tetraethyl orthosilicate, thereby improving the effect of the vinyl-terminated polydimethylsiloxane on reducing the surface energy of the fiber surface, thereby improving the softness of the soft skin-care fabric, and at the same time, the longer methoxysilane segment can promote the formation of silica gel and the adhesion of tetraethyl orthosilicate, thereby improving the hygroscopicity of the soft skin-care fabric;From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that Examples 1, 2, 3 have higher softness than Comparative Example 4, which indicates that the end-capping with triethoxysilane during the modification of the vinyl-terminated polydimethylsiloxane converts the vinyl groups at the ends of the modified vinyl-terminated polydimethylsiloxane into triethoxysilyl groups, thereby improving the binding efficiency and effect of the ends on the inorganic interface, thereby improving the softness of the soft skin-care fabric. ;
[0033] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a soft skin-care fabric, Features: The preparation process mainly includes the following steps: (1) In a nitrogen atmosphere, hydroxymethyltriethoxysilane, dimethyldimethoxysilane, methylvinyldimethoxysilane, anhydrous ethanol and 18% acetic acid were mixed in a mass ratio of 1:3.5:2:9:6, stirred at 35°C and 650 r / min for 70 min, and then hexamethyldisiloxane (3.5 times the mass of hydroxymethyltriethoxysilane) was added and stirred for 25 min. The mixture was allowed to stand for 12 min, and the oil phase was separated and allowed to stand at 20°C and 1.5 kPa for 9 h to obtain vinyl polysiloxane. 4-Hydroxythiophenol and ethylene The polysiloxane and tetrahydrofuran were mixed evenly in a mass ratio of 1:4.5:22, and triphenylphosphine with a mass of 0.02 times that of 4-hydroxythiophenol and diisopropyl azodicarboxylate with a mass of 0.02 times that of 4-hydroxythiophenol were added at 2°C, and the mixture was stirred at 20°C and 1800r / min for 10 hours. Then, hexamethyldisiloxane with a mass of 4.5 times that of 4-hydroxythiophenol and pure water with a mass of 7 times that of 4-hydroxythiophenol were added and the mixture was stirred for 25 minutes. The mixture was allowed to stand for 12 minutes, and the oil phase was separated and dried at 20°C and 5Pa for 9 hours to obtain mercaptovinyl polysiloxane. (2) Ferric chloride, ferrous chloride, tetrabutyl titanate and pure water were mixed in a mass ratio of 5:2:4.5:27, heated to 85°C in a nitrogen atmosphere, stirred at 1800 r / min for 4 min, added with 50% ammonia water (2.5 times the mass of ferric chloride), stirred at 1800 r / min for 18 min, filtered and washed with pure water for 4 times, dried at 65°C for 3.5 h, and composite nanoparticles were obtained. Composite nanoparticles, p-chlorophenyltrimethoxysilane, anhydrous ethanol and pure water were mixed in a mass ratio of 3.5:1:18:3.5, stirred at 20°C and 900 r / min for 45 min, and dried at -5°C and 5P a dried for 9 hours to obtain pre-modified composite nanoparticles, the pre-modified composite nanoparticles, mercaptovinyl polysiloxane, toluene and N-methylpyrrolidone were mixed uniformly in a mass ratio of 1:1.5:16:5.5, and then a 4% potassium hydroxide solution with a mass fraction of 1.1 times the mass of the pre-modified composite nanoparticles was added, stirred at 20°C and 400r / min for 25 minutes, heated to 125°C and maintained for 3.5 hours, and continued to heat to 165°C and maintained for 3.5 hours. After cooling to room temperature, 4% hydrochloric acid was added to adjust the pH to 7, filtered and washed with pure water and anhydrous ethanol for 4 times respectively, and dried at 20°C and 5Pa for 9 hours to obtain modified composite nanoparticles; (3) Poly (1,3-butadiene), TPU polyurethane, polyethylene terephthalate, modified composite nanoparticles, tetrahydrofuran, N,N-dimethylformamide, polyethylene glycol, and anhydrous ethanol were mixed uniformly in a mass ratio of 1:1:1:1:8:8:0.15:3, and subjected to electrospinning at a voltage of 18 kV, a spinning speed of 42 μL / min, a receiving distance of 16 cm, a spinneret aperture of 0.8 m, and a temperature of 52 °C to obtain a semi-finished fiber; (4) Vinyl-terminated polydimethylsiloxane and n-hexane were mixed evenly in a mass ratio of 1:6, and then 0.02 times the mass of vinyl-terminated polydimethylsiloxane and 0.6 times the mass of allyldimethoxysilane were added, and the mixture was stirred and refluxed at 75°C and 600 r / min for 5 hours. Then, 0.09 times the mass of vinyl-terminated polydimethylsiloxane was added, and the mixture was stirred and refluxed for 5 hours. The mixture was allowed to stand at 25°C and 1.5 kPa for 3.5 hours to obtain modified vinyl-terminated polydimethylsiloxane. The semi-finished fiber was immersed in a 25°C , in 65% ethanol by mass, use a 350W high-pressure mercury lamp to irradiate the semi-finished fiber with ultraviolet light for 4 minutes at a position 2.5 cm above the semi-finished fiber, continue to irradiate and add 0.35 times the mass of the semi-finished fiber of ethyl orthosilicate and 0.15 times the mass of the semi-finished fiber of modified terminal vinyl polydimethylsiloxane, ultrasonically treat at 35kHz for 35 minutes, take out and wash with pure water and anhydrous ethanol 4 times respectively, dry at -5℃, 5Pa for 9 hours to obtain soft skin care fiber, twist the soft skin care fiber to 60D through a fiber braiding machine, and weave it into 120g / m 2 Heavy weight fabric, made with UV protection and wrinkle resistance.
